Application of laparoscopy in the combined surgical procedures of gynecological and digestive disorders in obese women: A retrospective cohort study. (April 2015) - Wang, Haibo; Zhou, Ailing; Fan, Min; Li, Ping; Qi, Shengwei; Gao, Licai; Li, Xiujuan; Zhao, Jinrong
Abstract: Background: Laparoscopy surgery has been widely used for many decades and combined laparoscopic procedures have become favorable choices for concomitant pathologies in the abdomen. However, the type of combination procedures and their safety in obese women have not been well elucidated in obese women. Methods: Here we retrospectively reported 147 obese women underwent combined laparoscopic gynecological surgery and cholecystectomy/appendicectomy in our hospital from January 2003 to December 2011. Of the total number of patients (n = 147), various laparoscopic gynecological surgeries were combined with laparoscopic cholecystectomy in 93 patients, and were combined with laparoscopic appendectomy in the rest 54 patients. Patients' ages ranged from 24 to 55 years with an average of 33 years. Results: Our results showed that combined procedures caused various operative time and blood loss, with no difference considering the time to resume oral intake and length of hospital stay. Intraoperative complications occurred in a total of 7 patients (4.8%). None of the patients suffered from major complications after laparoscopic surgery, and minor postoperative complications occurred in 30 patients (20.4%). The follow-up period ranged from 6 to 24 months (average, 18.5 months). None of the patients developed complications during follow-up, except that one patient suffered from colporrhagia. Conclusions: Our results further suggest that the combined abdominal laparoscopic procedures of gynecologic and general surgery are safe and economic choices for obese women, and benefit patients in many ways including lesser pain, shorter hospital stays and earlier recovery. Highlights: Combined laparoscopic procedures for obese patients are difficult and less reported. 147 obese women underwent combined laparoscopic gynecological surgery and LC/LA. Combined procedures caused different operative time and blood loss. Time to resume oral intake and length of hospital stay are with no difference. The rate of complications was similar to that in patients with low BMIs.